Analisis Analisis Sistem Informasi Akuntansi dalam Pengendalian Keuangan dan Efisiensi Penjualan Pada Dealer Wuling Pontianak - Rumintar J. H. Marpaung; Suanti Suanti; Chici Askotamiya (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to analyze the implementation of the Accounting Information System (AIS) in financial control and sales efficiency at PT Arista Jaya Lestari (Wuling) Pontianak. This research employs a qualitative method with a case study approach. Data were collected through in-depth interviews with finance and sales staff, direct observation of transaction recording processes, and documentation analysis such as financial reports and standard operating procedures. Data were analyzed using the Miles and Huberman method, which includes data reduction, data display, and conclusion drawing. The result show that the implementation of the AIS through the Odoo, ADMS Kasir, and ADMS Unit applications has improved transaction accuracy, accelerated the preparation of financial reporting, and strengthened cash and receivable control. Furthermore, this digital system enchances sales efficiency by integrating data across departments, accelerating transaction processes, and facilitating real-time vehicle stock monitoring. The main challenges identified are limited user training and dependence on internet connectivity. Overall, this study concludes that the implementation of Odoo and ADMS based AIS improve the effectiveness of financia control and operational efficiency in the automotive sector.